Development of Indonesian Realistic Mathematics Education-Based Learning Module - Awalimahfuzoh, Rafiqa; Lubis, Marasamin; Siregar, Tanti Jumaisyaroh (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study aims to develop teaching materials in the form of Mathematics Modules Based on Indonesian Realistic Mathematics Education (PMRI) on the material of sequences and series in class VIII. The quality of the developed product is assessed based on aspects of the validity, practicality and effectiveness of the developed module. This research method uses the type of Research and Development (Research and Development) using a research design from the Borg and Gall procedure. The subjects of this study were students of class VIII Mts Negeri Labuhanbatu Utara, totaling 20 students. The results obtained are that the development of this module can improve student learning outcomes and understanding. The results of the validity of this module were tested from the validity of media experts and material experts getting an average score of 92.85% in the "very valid" category. Furthermore, the results of the practicality of this module were tested with student and teacher response questionnaires obtained an average score of 88.4% in the "very practical" category. In addition, the results of the effectiveness of the module product are tested with the Pretest - Posttest questions which are then calculated by the N - Gain Score test, while the students' average pretest score is 49.5 and the students' Posttest average score is 83.5, then the results of the N-Gain Score is 70.1% with the category "quite effective". So that the development of learning modules based on the Indonesian Realistic Mathematics Education Approach (PMRI) is said to be valid, practical and effective for use in class VIII SMP/MTS.